Neonate with VACTERL Association and a Branchial Arch Anomaly without Hydrocephalus - Velazquez, Danitza; Pereira, Elaine; Havranek, Thomas (American Journal of Perinatology Reports, 2016)
VACTERL (vertebral anomalies, anal atresia, cardiac defect, tracheoesophageal fistula, renal anomaly, limb anomalies) is an association of anomalies with a wide spectrum of phenotypic expression. While the majority of cases are sporadic, there is evidence of an inherited component in a small number of patients as well as the potential influence of nongenetic risk factors (maternal diabetes mellitus). Presence of hydrocephalus has been reported in VACTERL patients (VACTERL-H) in the past, with some displaying branchial arch anomalies. We report the unique case of an infant of diabetic mother with VACTERL association and a branchial arch anomaly—in the absence of hydrocephalus.
Keywords: VACTERL association; neonate; branchial arch anomaly; infant of diabetic mother